The inclination of the tibial component has an impact on fracture stability in unicompartmental knee arthroplasty: an artificial bone study - Wegner, Mathis; Bettendorff, Maximilian; Bruhn, Malte; Bahr, Jörg; Carstensen, Jürgen; Siebert, Leonard; Moradi, Babak (Frontiers in Bioengineering and Biotechnology, 2025)
BackgroundPeriprosthetic fractures (PPFs) following unicompartmental knee arthroplasty (UKA) are a significant clinical challenge. Tibial component positioning may influence fracture risk, but the biomechanical effects of varus inclination on fracture loading remain unclear.MethodsWe investigated the effect of tibial component varus inclination on fracture load using the Oxford® Partial Knee implant system, synthetic tibiae and a dynamic loading model. Tibial components were implanted at neutral (0°), 3° and 6° varus angles. Vertical loading was applied until fracture and fracture loads were compared between groups.ResultsA 3° varus position significantly increased fracture load by 34% compared to neutral (p < 0.05). No further statistically significant increase was observed at 6° varus. The dynamic model suggested that the mobile meniscal bearing may contribute to an improved load distribution, thereby increasing fracture resistance.ConclusionSlight varus inclination of the tibial component in UKA increases the medial tibial fracture load, potentially reducing the risk of PPF. Our findings highlight the biomechanical advantages of controlled varus positioning and provide insight into optimizing implant alignment.